The Development of Student Worksheets (LKPD) Based on Android on Observation Text Materials at Vocational School - Rukiyah, Siti; Puspita, Yenny (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to develop an Android-based Student Worksheet (LKPD) on observation text material to improve the effectiveness and involvement of students in learning Indonesian at SMK 'Aisyiyah Palembang. Using a research and development (R&D) approach with the ADDIE model comprising Analysis, Design, Development, Implementation, and Evaluation stages, the study involved language experts, material experts, media experts, and grade X students as users. Data collection employed observation, interviews, questionnaires, and learning outcome tests. The data consisted of qualitative information from observations, interviews, and student feedback, and quantitative data from expert validation scores, student practicality questionnaires, and pretest-posttest results. Data sources included the experts, students, and the Indonesian language teacher. Analysis involved calculating expert validation percentages to determine validity, questionnaire percentages for practicality, and comparing pretest and posttest scores for effectiveness, with normality tests ensuring statistical reliability. Validation scores showed the LKPD to be highly valid, with language experts rating 94%, media experts 95%, and material experts 97%. Practicality tests yielded 91% and 92% in individual and small group trials, respectively. Effectiveness was evident with a significant increase in average scores from 54.58 (pretest) to 83.33 (posttest). These results demonstrate that the Android-based LKPD is feasible, practical, and effective as innovative learning media supporting the Independent Curriculum and digital learning in vocational schools.